(untitled) (Fiep Bulletin - online, 2011)
Abstract: This article aims to deal about the evolution of human beings, the relationship with it´s own body, trying to understand the events that led to a mistaken separation of body and mind. This work also emphasizes it´s actions as being transformative, since the early days of human evolution to the present day, highlighting the ineffectiveness of certain expressiveness that is reflected in an inhuman and insensitive, since the mold is in the social environment. Self-knowledge, adding value that will serve for a better development.